APPLICATION OF SCIENCE LEARNING IN THE OPEN NATURE CLASS OF JUNIOR SCHOOL IT INSAN KAMIL, BIMA TOWN - Irfan, Muhammad (Prodi PGMI STIT Sunan Giri Bima, 2023)
By utilizing the surrounding environment as a learning resource students can easily master science concepts because students make observations in concrete situations. The positive impact of the environmental approach is that students can be motivated by their curiosity about something in their environment. Students will feel more challenged because students are dealing directly with real objects. Learning outcomes are very important because they become a benchmark for the extent to which the teaching and learning process takes place optimally. This study aims to determine the application of the application of natural science learning in the open air class of SD IT Insan Kamil, Bima City. This research is a type of field research, using qualitative research methods. 4. The average value of students in the skill aspect is higher than the knowledge aspect, with a skill value of 79 and knowledge of 81. This is because in the skills aspect, during Covid-19 learning students can easily learn science material at home. By collecting assignments based on students' skills, they directly learn natural science in the open.